Preoperative staging of uterine cancer: can transvaginal ultrasonography play a role? - Mariana Rei; Mariana Rei; Cristina Costa-Santos; Cristina Costa-Santos; João Bernardes; João Bernardes; João Bernardes; Antónia Costa; Antónia Costa (Frontiers in Oncology, 2023)
IntroductionPreoperative staging of uterine cancer has recently been implied as an important contribution to an accurate selection of low-risk cases, ultimately avoiding unnecessary lymph node debulking. The aim of this study was to evaluate the validity of transvaginal ultrasonography (TVS) in preoperative staging of uterine cancer in comparison to pelvic magnetic resonance imaging (MRI) and permanent section.MethodsWe conducted a prospective longitudinal multicenter trial between 2017 and 2018. Inclusion criteria comprised cases of endometrial neoplasia histologically confirmed or strong imaging suspicion, candidates for elective surgery as primary treatment. Proportions of Agreement (PA), kappa statistic (K), sensitivity, specificity and accuracy were calculated with 95% confidence intervals (95%CI).ResultsEighty-two patients were eligible for the study, presenting a mean age of 68 years (standard deviation 11). In what concerns the TVS evaluation of myometrial invasion, the subjective and objective methods of Gordon and Karlsson presented a sensitivity of 79%, 79% and 67% [95%CI 63-91; 63-91; 50-81], a specificity of 65%, 58% and 79% [95%CI 49-79; 42-73; 64-89] and an overall accuracy of 72%, 68% and 73% [95%CI 61-81; 57-78; 63-82]. MRI presented respectively a sensitivity, specificity and overall accuracy of 92%, 70% and 82% [95%CI 77-98; 52-85; 71-90]. Regarding cervical involvement, the sensitivity was respectively 31%, 50% and 67% [95%CI 9-61; 21-79; 35-90] for the subjective method, objective TVS and MRI, and the specificity was 98%, 90% and 100% [95%CI 92-100; 77-97; 94;100]. Agreement between TVS and MRI was superior in the assessment of cervical invasion, with PA ranging from 0.82 to 0.93 and K from 0.45 to 0.58, in comparison to myometrial invasion with PA ranging from 0.68 to 0.73 and K from 0.31 to 0.50. Considering the assessment of cervical involvement, as MRI showed a specificity of 100% it is not possible to increase the specificity. However, it was possible to increase the sensitivity, considering the combination of TVS with objective approach and MRI.ConclusionTVS may have a promising role as a tool for preoperative staging of endometrial carcinoma, presenting a performance that approximates to MRI, with a higher agreement in the assessment of cervical invasion.